Virtual reality tasks with eye tracking for mild spatial neglect assessment: a pilot study with acute stroke patients - Uimonen, Jenni; Villarreal, Sanna; Laari, Siiri; Arola, Anne; Ijäs, Petra; Salmi, Juha; Hietanen, Marja (Frontiers in Psychology, 2024)
Objective: Increasing evidence shows that traditional neuropsychological tests are insensitive for detecting mild unilateral spatial neglect (USN), lack ecological validity, and are unable to clarify USN in all different spatial domains. Here we present a new, fully immersive virtual reality (VR) task battery with integrated eye tracking for mild visual USN and extinction assessment in the acute state of stroke to overthrow these limitations. Methods: We included 11 right-sided stroke patients and 10 healthy controls aged 18 – 75 years. Three VR tasks named the Extinction, the Storage and the Shoot the target tasks were developed to assess USN. Furthermore, neuropsychological assessment examining various parts of cognitive functioning was conducted to measure general abilities. We compared VR and neuropsychological task performance in stroke patients – those with (USN+, n=5) and without USN (USN–, n=6) – to healthy controls (n=10) and tentatively reported the usability of VR system in the acute state of stroke. Results: Patients had mostly mild neurological and USN symptoms. Nonetheless, we found several differences between the USN+ and healthy control groups in VR task performance. Compared to controls, USN+ patients showed visual extinction and asymmetry in gaze behavior and detection times in distinct spatial locations. Extinction was most evident in the extrapersonal space and delayed detection times on the extreme left and on the left upper parts. Also, USN+ patients needed more time to complete TMT A compared with USN– patients and TMT B compared with controls. VR system usability and acceptance were rated high; no relevant adverse effects occurred. Conclusion: New VR technology with eye tracking enables ecologically valid and objective assessment methods with various exact measures for mild USN and thus could potentially improve future clinical assessments.